2021
DOI: 10.1007/s40265-021-01530-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Treatments, and Vaccine Development for Antimicrobial-Resistant Neisseria gonorrhoeae: Current Strategies and Future Directions

Abstract: Neisseria gonorrhoeae is the second most common bacterial sexually transmitted infection in the world after Chlamydia trachomatis . The pathogen has developed resistance to every antibiotic currently approved for treatment, and multidrug-resistant strains have been identified globally. The current treatment recommended by the World Health Organization is ceftriaxone and azithromycin dual therapy. However, resistance to azithromycin and ceftriaxone are increasing and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 180 publications
1
30
0
Order By: Relevance
“…Currently, the World Health Organization (WHO) has included N. gonorrhoeae as a high priority pathogen because of therapy failures and dramatic case number increases [ 2 ]. The pathogen has developed antimicrobial resistance (AMR) to every antibiotic currently approved for treatment [ 3 ], and the effectiveness of the last remaining option for first-line antimicrobial monotherapy, ceftriaxone, has come into question due to the evolving resistance and, especially, spread of the FC428 clone [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the World Health Organization (WHO) has included N. gonorrhoeae as a high priority pathogen because of therapy failures and dramatic case number increases [ 2 ]. The pathogen has developed antimicrobial resistance (AMR) to every antibiotic currently approved for treatment [ 3 ], and the effectiveness of the last remaining option for first-line antimicrobial monotherapy, ceftriaxone, has come into question due to the evolving resistance and, especially, spread of the FC428 clone [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of FC428, which is a globally disseminated ceftriaxone-resistant clone characterized by mosaic penA 60.001, has been widely documented, including in Japan, Denmark, South Korea, Ireland, Canada, Australia, Singapore, France and the UK, since 2015 [ 4 ], raising concerns about the long-term effectiveness of ceftriaxone therapy. In a study analyzing FC428 isolates from 2016 to 2019, the first case was identified in northern China (July 2016, Beijing) [ 5 ] and then FC428 disseminated to the central (2017 June to September, Hunan) [ 6 ], western (2018, Sichuan) [ 7 ] and eastern (May to October 2019, Zhejiang) [ 8 ] region, showing that highly resistant to ceftriaxone FC428 related clones had already appeared in China.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is a non-motile [ 9 ] and obligate-human pathogen [ 10 ] that can thrive aerobically or anaerobically in the presence of nitrite [ 11 ]. These diplococci, kidney-shaped bacteria infecting both men and women can cause the sexually transmitted disease (STD) named gonorrhea [ 12 , 13 ]. Every year, 87 million new infections are being reported for this quick-spreading contagious disease.…”
Section: Introductionmentioning
confidence: 99%
“…Every year, 87 million new infections are being reported for this quick-spreading contagious disease. This STD has already emerged as a major problem in low- and middle-income countries in Africa, Asia, Latin America, and the Caribbean [ 1 , 5 , 12 ]. Gonorrhea can be asymptotic or develop with symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation